Orelabrutinib plus reduced-dose whole brain radiotherapy in elderly primary central nervous system lymphoma: a case report - Wang, Qiao; Wang, Hua; Tang, Duozhuang; Wu, Yuanyuan; He, Siyao; Tao, Si (Frontiers in Oncology, 2025)
BackgroundPrimary central nervous system lymphoma (PCNSL) primarily affects elderly individuals, many of whom are unable to tolerate standard high-dose methotrexate (HD-MTX) chemotherapy due to frailty and comorbid conditions. There is a pressing need for alternative treatment strategies that offer reduced toxicity while maintaining therapeutic efficacy.Case presentationIn this case report, we describe three elderly patients (aged 70–78 years) with newly diagnosed, chemotherapy-ineligible PCNSL who were treated with a combination of reduced-dose whole brain radiotherapy (rd-WBRT, <30 Gy) and oral orelabrutinib (150 mg daily).ConclusionThese preliminary findings suggest that the all patients initially achieved either complete remission (CR) or partial remission (PR). Two patients maintained durable remission, whereas one patient experienced disease relapse after discontinuing orelabrutinib and switching to an alternative regimen. No significant neurotoxicity or treatment-related complications were observed. Combination of orelabrutinib and rd-WBRT may represent a safe and effective therapeutic approach for elderly patients with PCNSL who are not candidates for standard chemotherapy. Prospective clinical trials are warranted to further evaluate this approach.